2016
DOI: 10.1007/s12080-015-0291-7
|View full text |Cite
|
Sign up to set email alerts
|

Food web stability and weighted connectance: the complexity-stability debate revisited

Abstract: How the complexity of food webs relates to stability has been a subject of many studies. Often, unweighted connectance is used to express complexity. Unweighted connectance is measured as the proportion of realized links in the network. Weighted connectance, on the other hand, takes link weights (fluxes or feeding rates) into account and captures the shape of the flux distribution. Here, we used weighted connectance to revisit the relation between complexity and stability. We used 15 real soil food webs and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 35 publications
1
37
0
1
Order By: Relevance
“…On the same line, Thébault and Fontaine (2010) showed that stability of trophic networks is enhanced in weakly connected architectures. van Altena et al (2016) confirmed the role of weak interactions for stability of real food webs. However, given skewed distributions of Jacobian elements towards weak interactions, they found that stability was promoted by even distribution of fluxes over links, in contrast with de Ruiter et al (1995) and Rooney et al (2006) who emphasized the role of strong asymmetry.…”
Section: Strength Of Interactionsmentioning
confidence: 71%
See 2 more Smart Citations
“…On the same line, Thébault and Fontaine (2010) showed that stability of trophic networks is enhanced in weakly connected architectures. van Altena et al (2016) confirmed the role of weak interactions for stability of real food webs. However, given skewed distributions of Jacobian elements towards weak interactions, they found that stability was promoted by even distribution of fluxes over links, in contrast with de Ruiter et al (1995) and Rooney et al (2006) who emphasized the role of strong asymmetry.…”
Section: Strength Of Interactionsmentioning
confidence: 71%
“…Following a different perspective, Haydon (2000) focused on communities constructed to be as stable as they could be, and show that communities built in this way require high levels of weighted connectance, in agreement with van Altena et al (2016). According to these studies, high stability requires high connectance, especially between weakly and strongly self-regulated (intraspecific competition) elements of the community.…”
Section: Weighted Connectancementioning
confidence: 73%
See 1 more Smart Citation
“…Here, nodes, representing constituent taxa, were ordered along the vertical axis of the webs using respective trophic levels which we calculated with the NetIndices *1.4.4 statistical package (Kones et al ). We summarized all five webs with network topology indices representing ecologically relevant characteristics of their structure: (1) connectance (i.e., measure of overall complexity reflected in fraction of realized links over total possible links; Dunne et al a ); (2) maximum trophic level (i.e., measure of vertical complexity reflected in the highest trophic level occupied by a consumer in the food web; Digel et al ); (3) mean index of omnivory (i.e., measure of vertical complexity represented by average variation in trophic levels of prey items consumed by all heterotrophic taxa; Thompson et al ); (4) mean trophic level (i.e., measure of vertical distribution of taxa in the food web reflected in the average trophic level; Digel et al ); and (5) Gini's coefficient (i.e., measure of evenness in the distribution of trophic interaction strengths with upper and lower limits of zero and one, respectively, where a value of zero reflects perfect equivalence of interaction strength among links in the food web; van Altena et al ).…”
Section: Methodsmentioning
confidence: 99%
“…2015; Neutel & Thorne, 2014;Neutel et al, 2002Neutel et al, , 2007. Various studies have suggested alternative connectance measures which incorporate the strength of interactions (Banašek-Richter et al, 2009;Bersier et al, 2002;Ulanowicz, 1997;Van Altena, Hemerik, & de Ruiter, 2016). Furthermore, it has been argued that in order to understand community stability, we need to look at the feedback structure formed by the interactions (Levins, 1974) and quantify critical feedback loops (Neutel et al, 2002).…”
mentioning
confidence: 99%